Investigar la incorporación de hijos de migrantes a través de Respondent Driven Sampling (RDS) - Gómez, Pablo Sebastián; Iglesias, Maximiliano (El Colegio de México, 2021)
In the field of migration studies, one long-standing research topic is the study of the “second generations” or “children of migrants.” In this paper, we present the methodological problems derived from the generation of primary data on the issue. First, the population is small and traditional surveys do not capture the information. Second, since we do not have an exhaustive list of member, the sampling frame is inadequate. Here we develop a viable alternative to solve these problems: Respondent-Driven Sampling (RDS) for the study of the processes of incorporating the children of migrants in general and the children of South-South migrants in particular.